Effects of a respiratory functional training program on pain and sleep quality in patients with fibromyalgia: A pilot study. (August 2017) - Garrido, M.; Castaño, M.Y.; Biehl-Printes, C.; Gomez, M.A.; Branco, J.C.; Tomas-Carus, P.; Rodriguez, A.B.
Abstract: Objective: To evaluate the effect of 8-week respiratory functional training program on pain tolerance, sleep, and urinary antioxidant and cortisol levels in 18 patients with fibromyalgia. Methods: Participants underwent a 12-week intervention: 4 weeks as control and 8 weeks of breathing exercises. Pain tolerance assay was done by using an algometer, whereas sleep quality was evaluated by actigraphy and by the Pittsburgh Sleep Quality Index. Cortisol and antioxidant levels were determined using commercial assay kits. Results: Increases in the pain tolerance threshold were detected in the occiput point after one month of intervention as well as in the low cervical and second rib points after one and two months. Actigraphy revealed a decrease in sleep latency, whereas sleep questionnaire showed improvements in sleep quality, sleep duration and sleep efficiency. No changes in cortisol and antioxidant levels were detected. Conclusion: The 8-week breathing exercise intervention reduced pain and improved sleep quality. Highlights: An 8-week breathing exercise intervention ameliorates the threshold of pain tolerance in patients with fibromyalgia. The breathing exercise intervention enhances sleep quality in fibromyalgia. A breathing exercise intervention is proposed to ameliorate some fibromyalgia-related symptoms.